Snail coprophagy: the encounter filter, food preferences, and rat lungworm (Angiostrongylus cantonensis) prevalence - Rollins Randi L.; Griffin Chasen D.; Cowie Robert H. (Parasite)
Understanding the factors driving infection prevalence among host species is crucial for effective disease mitigation. Angiostrongylus cantonensis, the rat lungworm, causes neuroangiostrongyliasis and serves as an excellent model for studying infection dynamics across hosts. This study investigates the relative impact of encounter rates on A. cantonensis prevalence in snail hosts by assessing their coprophagic tendencies. Multiple-choice feeding assays were conducted with four snail species (Parmarion martensi, Laevicaulis alte, Lissachatina fulica, and Veronicella cubensis) differing in A. cantonensis prevalence. The snails were offered romaine lettuce, hibiscus flowers, papaya, and rat feces. The relative intake ratios (RIR) were calculated and used to evaluate 1) feces preference among the snail species, and 2) correlation between feces preference and A. cantonensis prevalence. We also compared preferences for feces from rats fed high-fat and balanced diets; no significant difference was observed. Feces made up the highest proportion of the diet of P. martensi (11.6%), followed by V. cubensis (7.8%), L. fulica (5.9%), and L. alte (5.1%). Additionally, P. martensi showed a significantly higher preference (RIR) than all other species. The correlation between feces preference and A. cantonensis prevalence among species was weakly positive. These findings suggest that the level of coprophagy influences encounter rates with A. cantonensis, contributing to variation in infection prevalence among snail species. However, other factors may also play a role, as preference and prevalence were only weakly correlated. Understanding these dynamics can inform strategies for managing the spread of A. cantonensis and mitigating its health impacts.